Performance analysis of MAC layer scheduling schemes for IMM applications over high speed wireless campus network in IEEE802.11e - Alam, Md Korshed; Abd Latif, Suhaimi; Akter, Mahmuda; Arafat, M. Y.; Hakak, Saqib Iqbal (Informatics (India) Ltd., 2015)
In IMM traffic, while establishing a voice or video conversation, the sender and the receiver (the participants) should be mutually benefited by ensuring QoS like minimum data loss, sharing sufficient bandwidth and achieving high throughput over the WCN. To improve the network performance, scheduling mechanism is a challenging issue in the transmission of IMM traffic and it still needs to be solved over WCN. This paper aims to employ three different MAC layer scheduling mechanisms such as FIFO, RED and WRED for analysing the performance over the network, based on variation of traffic load in IEEE802.11e, and to evaluate the proposed schedulers’ performance using different performance metrics in WCN. Here, the traffic load is varied by increasing the packet size and the traffic arrival rate, respectively. In order to analyse the network performance, the simulation has been done in QualNET 5.1 simulator. In the simulator, the mobility model is chosen as ‘Random Waypoint’ to change the node position randomly and the application as CBR. Simulation results show that increasing the packet size enables RED and WRED schedulers to perform better than FIFO in terms of all the performance metrics. On the other hand, increasing the traffic arrival rate helps to enhance the performance of the FIFO scheduler compared to the FIFO scheduling mechanism in the previous case. It is conclusive through the performance analyses that all three schedulers perform comparatively better when the traffic arrival rate is increased compared to increasing the packet size.